ECOTOURISM PREFERENCE AND WILLINGNESS TO PAY: A CHOICE EXPERIMENT - Fitrotul Laili; Anisa Aprilia; Yusri Fajar; Shofwan Shofwan (Socio-Economics/Agribusiness Department, 2023)
Using a discrete choice research method, this research aims to determine visitors' preferences and willingness to pay (WTP). This study evaluates the entrance price, restaurant facilities, the quality of the offered information, and the tour price (per person). The selected respondents were tourists who had visited an ecotourism place at least once. The study yielded the highest WTP based on the desire for restaurant availability in the tourism region of Jolotundo. Tourist satisfaction as indicated by preferences and WTP is crucial data for tourism area managers to use in order to better meet visitor expectations.